THE POSITION OF EXHIBITIONIST PERPETRATOR IN CRIMINAL LAW - Edgar Pratama Hanibal; Sapta Aprilianto (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Exhibitionism is the act of exposing deliberately to the public the body parts of a person which are normally covered for example; breast, genitals, or buttocks. However, so far it still becomes a controversial whether this action is a criminal act that has consequences or not because of its existence which is considered as a disease. This study aims to find out whether the act of exhibitionism is a criminal act and how the perpetrator is responsible to his action. The type of the study used was legal (normative) research. Exhibitionist acts in Indonesian laws and regulations could be regulated in the Article 281 and the Article 289 to the Article 296 of the Criminal Code, the Article 81 and the Article 82 of Law Number 35 of 2014 concerning Child Protection, Article 10 and Article 36 of Law Number 44 of 2008 concerning Pornography